Survivability of hospitalized chronic kidney disease (CKD) patients with moderate to severe estimated glomerular filtration rate (eGFR) after experiencing adverse drug reactions (ADRs) in a public healthcare center: a retrospective 3 year study - Monica Danial; Mohamed Azmi Hassali; Loke Meng Ong; Amer Hayat Khan (BMC, 2018)
Abstract Background Accurate identification and routine preventive practices are crucial steps in lessening the incidence of medications and patients related adverse drug reactions (ADRs). Methods Three years retrospective study was conducted among chronic kidney disease (CKD) patients at multi-wards in a tertiary healthcare center. Data collected included demographic characteristics, physical examination results, comorbid conditions, laboratory tests and medications taken. Only medication prescribed during the hospital stay were considered in this study. Results From this study only one ADR incident was definitely preventable and majority of other ADRs (88.3%) were possibly preventable. Type of renal replacement therapy (p = 0.023) and stages of renal function (p = 0.002) were significantly associated with survivability of the hospitalized CKD patients after ADRs. Highest percentage of mortality based on categories were 50-59 years (20.0%), male (16.3%), Indian ethnicity (23.7%), obese (15.0%), smoking (17.1%), consumes alcohol (17.4%), conservative management of renal disease (19.5%) and renal function of < 15 mL/min/1.73m2. Overall survivability using Kaplan-Meier analysis reported a significant difference of 18-day survival rate between patients undergoing hemodialysis and patients conservatively managing their renal disease. The 18 days survival rate of patients undergoing hemodialysis, peritoneal dialysis and conservative management were 94.9%, 91.7% and 75.1% respectively. Eighteen days survival rate of patients with renal functions of 30-59 mL/min/1.73m2, 15-29 mL/min/1.73m2 and < 15 mL/min/1.73m2 were 87.4%, 69.8% and 88.6% respectively. Similarly, Cox regression analysis revealed that renal replacement therapy was the only factor significantly contributed to ADRs related mortality. CKD patients whom conservatively managed renal disease or/and with renal function of < 15 mL/min/1.73m2 had 5.61 and 5.33 higher mortality risk respectively. Conclusion Majority of the reported ADRs were possibly preventable. Renal replacement therapy and/or renal function were significant risk factors for mortality due to ADRs among hospitalized CKD patients stages 3 to 5. Clinician engagement, intensive resources and regular updates aided with online monitoring technology are needed for enhancing care and prevention of ADRs among CKD patients.